2022
DOI: 10.1002/ame2.12257
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gut microbiota in representative mice strains: Implications for biological research

Abstract: Background: Experimental animals are used to study physiological phenomena, pathological mechanisms, and disease prevention. The gut microbiome is known as a potential confounding factor for inconsistent data from preclinical studies. Although many gut microbiome studies have been conducted in recent decades, few have focused on gut microbiota fluctuation among representative mouse strains.Methods: A range of frequently used mouse strains were selected from 34 isolation packages representing disease-related an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Our results in the blood–CSF barrier complement previous studies that found germ‐free mice have lower tight junction protein expression in the BBB (Braniste et al, 2014), further implicating the gut microbiota in the regulation and maintenance of brain barrier integrity. Although we did not measure the gut microbiota composition in this study, the conventional mice were all raised under the same variables known to influence the gut microbiota composition (i.e., diet and light cycles) (Guo et al, 2022). Additionally, even if we were to have seen variation in microbiota composition among the conventional mice, we did not see different clusters in ZO‐1 network quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in the blood–CSF barrier complement previous studies that found germ‐free mice have lower tight junction protein expression in the BBB (Braniste et al, 2014), further implicating the gut microbiota in the regulation and maintenance of brain barrier integrity. Although we did not measure the gut microbiota composition in this study, the conventional mice were all raised under the same variables known to influence the gut microbiota composition (i.e., diet and light cycles) (Guo et al, 2022). Additionally, even if we were to have seen variation in microbiota composition among the conventional mice, we did not see different clusters in ZO‐1 network quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Some strains show resistance to the infection, while others show sensitivity to the infection, presumably due to the genetic diversity of the CC founders (mouse being the most commonly used animal model) 45 . This demonstrates the ability of the CC resource to provide high‐resolution mapping of QTL affecting a wide variety of traits, including susceptibility to a spectrum of infectious diseases 36,46,47 …”
Section: Resultsmentioning
confidence: 99%
“…Both diets used are considered standard rodent chow, but the extruded diet lacks fish meal and soy products (S1 Table ), which can be a source of the pro-inflammatory molecules nitrosamines and isoflavones [27][28][29]. Genetic background and sex influences barrier formation, DSS sensitivity, microbiome composition and cytokine expression [30][31][32][33]; therefore, to reduce their confounding effects, we used isogenic C57BL/6 male mice for all DSS treatment analyses unless otherwise stated. Mice were housed under each respective housing condition for a minimum of 4 weeks before treatment with 1% or 2.5% DSS.…”
Section: Resultsmentioning
confidence: 99%